2014
DOI: 10.1016/j.neuroimage.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the structure and function of prefrontal cortex–amygdala circuitry in children and adolescents: A multi-modal imaging approach

Abstract: The uncinate fasciculus is a major white matter tract that provides a crucial link between areas of the human brain that underlie emotion processing and regulation. Specifically, the uncinate fasciculus is the major direct fiber tract that connects the prefrontal cortex and the amygdala. The aim of the present study was to use a multi-modal imaging approach in order to simultaneously examine the relation between structural connectivity of the uncinate fasciculus and functional activation of the amygdala in a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 54 publications
(85 reference statements)
12
139
4
1
Order By: Relevance
“…Posthoc Student's t tests between genotypes within each age group showed enhanced projections from IL to BLA in adolescent [t(12) = 13.81; P < 0.0001] and adult [t(12) = 12.49; P < 0.0001] FAAH A/A mice relative to FAAH C/C mice but no differences in fiber density in preadolescent mice [t(12) = 0.56; P = 0.583] as a function of FAAH C385A genotype. Prior studies have shown that anxiety disorders peak during adolescence (1, 2) when there are dynamic changes in AEA levels (10, 11) that impact anxiety-related frontolimbic circuitry (28)(29)(30)(31). Moreover, we have shown that the FAAH A385 allele is associated with increased frontolimbic connectivity and lower anxiety in both mice and humans in adulthood (14).…”
Section: Faah C385a-associated (Phenotypic) Differences In Frontolimbmentioning
confidence: 55%
“…Posthoc Student's t tests between genotypes within each age group showed enhanced projections from IL to BLA in adolescent [t(12) = 13.81; P < 0.0001] and adult [t(12) = 12.49; P < 0.0001] FAAH A/A mice relative to FAAH C/C mice but no differences in fiber density in preadolescent mice [t(12) = 0.56; P = 0.583] as a function of FAAH C385A genotype. Prior studies have shown that anxiety disorders peak during adolescence (1, 2) when there are dynamic changes in AEA levels (10, 11) that impact anxiety-related frontolimbic circuitry (28)(29)(30)(31). Moreover, we have shown that the FAAH A385 allele is associated with increased frontolimbic connectivity and lower anxiety in both mice and humans in adulthood (14).…”
Section: Faah C385a-associated (Phenotypic) Differences In Frontolimbmentioning
confidence: 55%
“…Previously, lower uncinate fasciculus integrity was associated with greater amygdala reactivity in response to fearful faces in healthy participants 56 and in response to happy and sad faces in children and adolescents (aged 9-19 yr). 57 Moreover, lower structural uncinate fasciculus tract integrity in patients with generalized social anxiety disorder (compared with healthy controls) was associated with decreased functional amygdala to vmPFC connectivity. 58 In our study, we observed vmPFC deactivation toward emotional faces.…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, the studies described so far collectively show that childhood is a developmentally unique period for parental buffering of CORT, emotional responding, amygdala reactivity, and amygdala-mPFC connectivity (see, eg, Decety et al, 2012;Egliston and Rapee, 2007;GabardDurnam et al, 2014;Gee et al, 2013bGee et al, , 2014Hibel et al, 2014b;Middlemiss et al, 2012;Sullivan, 2004, 2006;Papp et al, 2009;Seltzer et al, 2010Seltzer et al, , 2012Silvers et al, 2014;Sorce et al, 1985;Sullivan et al, 2000;Swartz et al, 2014;Vink et al, 2014). Importantly, we believe that the role of the parent in phasic modulation of the amygdala and mPFC is critical for circuit tone and for the long-term effectiveness of the circuit in emotion regulation.…”
Section: Phasic Parental Modulation Of Amygdala-prefrontal Circuitsmentioning
confidence: 88%
“…Specifically, amygdala connectivity with mPFC changes from nonsignificant coupling to being positively coupled, as children transition into adolescence (∼10.5 years of age; Gabard-Durnam et al, 2014; NB: patterns of resting connectivity are often opposite in valence to task-based patterns, suggesting that resting connectivity may function to prime the circuit for expected connectivity patterns during tasks). In addition, structural integrity of the uncinate fasciculus (the major white matter tract connecting the PFC and amygdala) increases across age and predicts reduced amygdala reactivity to pictures of emotion-expressing faces (Swartz et al, 2014). Importantly, the maturation of prefrontal cortical regions and increase in connectivity between amygdala and PFC also appears to have direct consequences for emotional functioning in childhood.…”
Section: Pfc Developmentmentioning
confidence: 99%